Myanmar character extraction from vehicle images using aspect ratio and bounding box - Khin, Ohnmar; Phothisonothai, Montri; Choomchuay, Somsak (My University, 2018)
In this paper, we publicize Myanmar character extraction system using the license plate number as experimental sample. In recent times, the identification of car license becomes a popular task because of the increase in the number of vehicles. To settle this problem, there are a number of techniques in which aspect ratio and bounding box are the suitable technology. We also use edge boxes in order to separate the background from the foreground and accentuate in the foreground. In the investigation, the Myanmar character are segmented firstly and then these are extracted precisely. The experimental results showed that the characters have been correctly extracted by the accuracy rate of 90%.
Keywords: aspect ratio; bounding box; number plate extraction